Optical link for stereo headphones / Abdul Latif Hasan - Hasan, Abdul Latif (1989)
Optical link for the stereo headphone is a personal headphone receiver with safe non-interferencing infrared (IR) optical link back to the transmitter. It solve the problem of long cable. It is used by simply plugging the transmitter into the TV's earphone socket.